AGROBACTERIUM-MEDIATED TRANSFORMATION OF TWO TOMATO CULTIVARS (LYCOPERSICON ESCULENTUM MILL.) CV. SANDRA AND ROCKY - Danial, G. H.; Ibrahim, D. A.; Song, G. Q. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
An efficient protocol for Agrobacterium-mediated transformation of tomato cultivars Sandra and Rocky was conducted to examine the possibility of producing transgenic tomato plants cultivars harbouring the nptII gene, conferring kanamycin resistance. To achieve this aim, tomato cotyledon explants were transformed using EHA105 Agrobacterium tumefaciens strain harboring the binary vectors pBI121 which contains Gus gene, and neomycin phosphotransferase II (nptII) as selectable marker gene under the control of a CaMV35S promoter and nopaline synthase (nos) Terminator. Transformant detection was carried out in three distinct ways. First antibiotic selection, Kanamycin at a concentration of100 mgl-1 found to be efficient for this purpose. Second histochemical GUS assay revealed the presence of blue colored zones in a number of shoots and leaves for both in vitro and the greenhouse-grown transgenic plants. Third PCR analysis indicated positive result by showing the fragment for nptII gene in tested transformants, while was absent in non-transgenic control (wild type). On the other hand, the results showed that Sandra cultivar was more efficient for regeneration and subsequently transformation frequency than Rocky cultivar, which record 26.66% of transformation frequency compared with 11.57% in Rocky cultivar.